A New Species of Werauhia (Bromeliaceae: Tillandsioideae) from Montane Cloud Forests of Costa Rica - Cascante Marín, Alfredo (2023)
Werauhia oenophylla Cascante & J. F. Morales (Bromeliaceae), a new species of Tillandsioid epiphytic bromeliad, is described from the montane forests of Costa Rica. The new species is related to W. umbrosa (L. B. Sm.) J. R. Grant by its compound inflorescence with several flowers in short (< 10 cm) lateral branches and coriaceous floral bracts that are longer than the pedicel. Werauhia oenophylla is distinguished by the combination of reddish-wine coloration on the abaxial surface of leaves and peduncle bracts and reddish-rose floral bracts. This species is only known from the country’s cloud forests in the Central Volcanic Mountain Range.